Management of end-stage heart failure patients with or without ventricular assist device: an observational comparison of clinical and economic outcomes. (26th July 2017) - Aissaoui, Nadia; Morshuis, Michiel; Maoulida, Hassani; Salem, Joe-Elie; Lebreton, Guillaume; Brunn, Matthias; Chatellier, Gilles; Hagège, Albert; Schoenbrodt, Michael; Puymirat, Etienne; Latremouille, Christian; Varnous, Shaida; et al.
Abstract: OBJECTIVES: Heart transplantation (HT) and ventricular assist devices (VAD) for the management of end-stage heart failure have not been directly compared. We compare the outcomes and use of resources with these 2 strategies in 2 European countries with different allocation systems. METHODS: We studied 83 patients managed by VAD as the first option in Bad Oeynhausen, Germany (Group I) and 141 managed with either HT or medical therapy, as the first option, in Paris, France (Group II). The primary end-point was 2-year survival. Kaplan–Meier analyses were performed after the application of propensity score weights to mitigate the effects of non-random group assignment. The secondary end-points were resource utilization and costs. Subgroup analyses were performed for patients undergoing HT and patients treated with inotropes at the enrolment time. RESULTS: The Group I patients were more severely ill and haemodynamically compromised, and 28% subsequently underwent HT vs 55% primary HT in Group II, P  <   0.001. The adjusted probability of survival was 44% in Group I vs 70% in Group II, P  <0.0001. The mean cumulated 2-year costs were €281 361 ± 156 223 in Group I and €47 638 ± 35 061 in Group II, P <  0.0001. Among patients who underwent HT, the adjusted probability of survival in Group I ( n = 23) versus Group II ( n = 78) was 76% versus 68%, respectively (0.09), though it differed in the inotrope-treated subgroups (77% in Group I vs 67% in Group II, P  = 0.04). CONCLUSIONS: HT should remain the first option for end-stage heart failure patients, associated with improved outcomes and better cost–effectiveness profile. VAD devices represent an option when transplant is not possible or when patient presentation is not optimal.